2017
DOI: 10.1038/s41467-017-02405-3
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-regulated decommissioning of multimeric PP2A complexes

Abstract: Dynamic assembly/disassembly of signaling complexes are crucial for cellular functions. Specialized latency and activation chaperones control the biogenesis of protein phosphatase 2A (PP2A) holoenzymes that contain a common scaffold and catalytic subunits and a variable regulatory subunit. Here we show that the butterfly-shaped TIPRL (TOR signaling pathway regulator) makes highly integrative multibranching contacts with the PP2A catalytic subunit, selective for the unmethylated tail and perturbing/inactivating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 64 publications
3
52
3
8
Order By: Relevance
“…A recent structural study found that TIPRL binds specifically to the demethylated PP2A tail and perturbs the conformation and chelation of catalytic metal ions at the active site, resulting in phosphatase inactivation. That means methylation serves as a signaling switch that prevents TIPRL from interacting with PP2A or inactivating the PP2A active site (Wu et al, ). An additional study also indicated methylation sensitivity of TIPRL in cells (Nakashima et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent structural study found that TIPRL binds specifically to the demethylated PP2A tail and perturbs the conformation and chelation of catalytic metal ions at the active site, resulting in phosphatase inactivation. That means methylation serves as a signaling switch that prevents TIPRL from interacting with PP2A or inactivating the PP2A active site (Wu et al, ). An additional study also indicated methylation sensitivity of TIPRL in cells (Nakashima et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in both the DNA damage network and in a co-dependency network derived from the DepMap project (Tsherniak et al, 2017) (Figure 6B), CYB5R4 is connected to Ser/Thr phosphatases and phosphatase regulators such as PPP2R4 and TIPRL, which encode proteins that regulate the assembly and disassembly of PP2A-family holoenzymes, respectively (Guo et al, 2014;Wu et al, 2017). Like those targeting CYB5R4, sgRNAs against PPP2R4 caused clear sensitization to CPT (Figures 6C, S6F and Table S6) and thus we speculate that CYB5R4 regulates the response to DNA damage indirectly via the modulation of PP2A-family phosphatases.…”
Section: Cyb5r4 As a Candidate Modulator Of Protein Phosphatasesmentioning
confidence: 99%
“…In this manner Tip41p functions to activate PP2A-like catalysis by opposing Tap42. The mammalian ortholog of Tip41p, called TIPRL, on the other hand, cooperates with α4 (mammalian Tap42p) to promote mTORC activity by inhibiting the PP2A/4/6 phosphatases (58). In particular TIPRL and α4 together bind to holoenzymes and displace metal ions from the active site of the catalytic subunit to produce a latent yet stable complex.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, during its biogenesis, PP2Ac is bound by PTPA which helps to configure the active site for serine/threonine phosphatase activity (53, 115). Later, PP2Ac and PP4c may be inactivated by PME1 or by the coordinated function of TIPRL and α4 (homologues of S. cerevisiae Tip41p and Tap42p, respectively) that expel metal ions from the active site (58,59,116). When bound by these negative regulators, catalytic subunits or holoenzymes are maintained in a stable latent state.…”
Section: Discussionmentioning
confidence: 99%